PENDAMPINGAN PASTORAL KRISTIANI BAGI KELUARGA YANG BERDUKA AKIBAT KEMATIAN KARENA COVID-19 - Yuansari Octaviana Kansil; Meily Meiny Wagiu (POIMEN Jurnal Pastoral Konseling, 2021)
The Covid-19 pandemic undermines all aspects of ecclesiastical services. This also has an impact on grieving services. There is no longer any consolation service held the same as before the pandemic. What is even sadder is that if a family member of the congregation dies of Covid-19, it makes them very sad. As a result of Covid-19, there is no longer the usual consolation worship that strengthens families. Because of this, pastoral care is very much needed, especially for families who are grieving. This paper uses a qualitative method with a literature study approach related to pastoral care. The results of the discussion are that the results of the discussion are to present forms of pastoral assistance for families who are grieving through family visits in which there are intense conversations with families. The conversation can use social media, video calls. In the mentoring process, the Pastor patiently listened to the expressions of grief that enveloped them and the Pastor in assisting them to carry out guidance, feelings of reconciliation, and healing through God's Word to families grieving due to Covid-19.